How Female Principals Communicate: Verbal and Nonverbal Micropolitical Communication Behaviors of Female Anglo and Hispanic School Principals - Carolyn S. Carr (Educational Considerations, 1995)
None [of these principals] had adopted male behaviors entirely, but all had relaxed the stereotypic restrained and closed female behaviors and speech reported in research of two decades ago.